Are sponge cities the solution to China's growing urban flooding problems?. (5th October 2022) - Fu, Guangtao; Zhang, Chi; Hall, Jim W.; Butler, David
Abstract: Nature‐based solutions have been promoted as a sustainable solution for urban stormwater management and they are currently adopted at an unprecedented speed and scale to build sponge cities in China, with a primary aim to solving urban flood problems. However, there are limits to how much rainfall sponge cities can absorb, hence, they are unlikely to be a panacea for flooding problems in cities. We argue that bottom‐up community‐based measures are essential part of the intervention development framework that is required to transform sponge cities into flood resilient cities. This community‐based approach can effectively build on the distinctive and unique feature of Chinese cities, that is, the prevalence of gated communities, which provides a solid foundation for implementing community‐based measures for flood management. A range of such community‐based measures including resilience mapping, property‐based resistant and resilient measures, flood insurance, and social resilience building are discussed. Flood resilience building does not just mean investments in gray–green–blue infrastructure, it requires social transformation toward flood resilient communities. This article provides a roadmap for the next stage development of sponge cities which plays a key role in coping with extreme storm events and adapting to climate change in cities. This article is categorized under: Engineering Water > Sustainable Engineering of Water Engineering Water > Planning Water Science of Water > Water Extremes Abstract : Integrating community resilience into gray‐green‐blue infrastructure for flood‐resilient sponge cities.